1937
DOI: 10.1002/ange.19370500404
|View full text |Cite
|
Sign up to set email alerts
|

Über den Einfluß der Elektrolyte auf die Reduktion von Nitraten mit Kupfer‐Magnesium und Kupfer‐Zink‐Staub

Abstract: d e r P r e u p . M o o r -V e r s u c h s s t a t i o n zu B r e m e nvon Dungesalzen -Slickatoffbeetimmu$ a18 Ammoniak rnit na&ierendern W a s a e r s~f / . Ring@. 19. August 1936 or kurzem haben wir in dieser Zeitschriftl) uber die Reduktion von Nitraten rnit Cu-Zn-Staub berichtet. Eine Abanderung der Arbeitsvorschrift sicherte eine leichte und einwandfreie Durchfiihrung der Analyse. Jetzt wurde der EinfluJ3 aller anwendbaren Elektrolyte auf den Reaktionsverlauf untersucht, um zu priifen, ob die gewtihlt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1938
1938
1967
1967

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Copper had a slight depressive action on manganese and a stimulative action on the assimilation of iron, under the conditions of their experiments. Arnd and Hoffman(15) and Coleman and Kuprecht(119) reported that fertilization…”
mentioning
confidence: 99%
“…Copper had a slight depressive action on manganese and a stimulative action on the assimilation of iron, under the conditions of their experiments. Arnd and Hoffman(15) and Coleman and Kuprecht(119) reported that fertilization…”
mentioning
confidence: 99%